PENGARUH POLA MAKAN TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR NEGERI 2 TUGURAJA - Melania, - (2022)
A good dietary habit should be accompanied by balanced nutrition. Means that elementary students needs a balanced nutrition for their body daily. Beside giving energy, a nutritional food also can affect to brain development, means if student consumes fewer nutritional foods can affect to their metabolism and moreover to learning achievement. This research aims to know the correlation between dietary habit and learning achievement, moreover how big the contribution of the dietary habit to the learning achievement in elementary school 2 Tuguraja. This research is quantitative research using survey method. Data processing is using scoring system, result of this research shows that 48 students got good remark (34%), Most of the learning achievement students at SDN 2 Tuguraja is in the medium category, amounting to 58 students (41%). In testing the hypothesis, a correlation test is carried out which has sig values. (2-tailed) 0,000 < 0,05. Means, there is a correlation between dietary habit and learning achievement. And, pearson correlation shows 0,568 which classified in medium category and it has 32,3% contribution.